2018
DOI: 10.33314/jnhrc.v16i2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Pregnant Women and Mothers of Children Under one Year in Sindupalchowk District

Abstract: Background: Common mental disorders such as anxiety and depression among mothers of young children and expectants can silently deteriorate the health of the mother with significant impact on the newborn. The primary aims were to determine the proportion of pregnant women and mothers of children under one year with anxiety and depression and their associated factors in Sindhupalchowk.Methods: We used the Hopkins Symptom Checklist 25 and a structured questionnaire in a cross-sectional study to collect informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The prevalence of depression among pregnant women was found to be 24.8%, which is similar to the estimate of antenatal depression suggested for South Asia by a meta-analysis, approximated at 25.0% 17. The observed prevalence rate of antenatal depression is similar to a cross-sectional study from Sindhupalchowk district, Nepal, where 23.8% of pregnant women were found to be depressed in the year 2015 19. However, the current prevalence is higher than the prevalence of antenatal depression noted among the women visiting public health facilities for antenatal checkups in Kathmandu, which was 18% in the year 2017 18.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The prevalence of depression among pregnant women was found to be 24.8%, which is similar to the estimate of antenatal depression suggested for South Asia by a meta-analysis, approximated at 25.0% 17. The observed prevalence rate of antenatal depression is similar to a cross-sectional study from Sindhupalchowk district, Nepal, where 23.8% of pregnant women were found to be depressed in the year 2015 19. However, the current prevalence is higher than the prevalence of antenatal depression noted among the women visiting public health facilities for antenatal checkups in Kathmandu, which was 18% in the year 2017 18.…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with the study from Sindhupalchowk district of Nepal where women with unplanned pregnancy were found to have threefold increase in odds of depression (AOR: 3.43, 95% CI: 1.78 to 6.62) as compared with women with planned pregnancy. 19 Similarly, another study from Pakistan also shared a similar finding, where women with unintended pregnancy had almost twice the odds (AOR: 1.94, 95% CI: 1.40 to 2.69) of depression. 38 Likewise, a study from Ethiopia also revealed that pregnant women who had not planned their pregnancy were six times more likely to be depressed than those who planned their pregnancy.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations